(untitled) (Raparin Journal of Humanities (RJH), 2023)
This research, titled "The Relationship between Public International Law and Domestic law in the Perspective of Treaties and International Caselaw and the Effects of Globalization - Analytical Study-" tries to highlight the relationship between public international law and domestic law from the point of view of international treaties and international caselaw, through the judgments of international arbitration, Permanent Court of International Justice and the International Court of Justice, as well as the positions of international criminal tribunals, and it examines the changes in this relationship as a result of the effects of globalization. Through this endeavor, it was concluded that the position of international treaties has been and continues to prevail over domestic laws when there is a conflict or collision between their rules, and along with international legal provisions, there is an abundant caselaw that have supported the position of international treaties in this regard. Moreover, globalization has affected the relationship between public international law and domestic law by trying to unify international legal rules and domestic laws, and then work to build a unified legal block that is not assigned to a specific geographical spot.